One Hundred Semesters : My Adventures as Student, Professor, and University President, and What I Learned along the Way - Chace, William M. (Book collections on Project MUSE., 2006)
In One Hundred Semesters, William Chace mixes incisive analysis with memoir to create an illuminating picture of the evolution of American higher education over the past half century. Chace follows his own journey from undergraduate education at Haverford College to teaching at Stillman, a traditionally African-American college in Alabama, in the 1960s, to his days as a professor at Stanford and his appointment as president of two very different institutions--Wesleyan University and Emory University. Chace takes us with him through his decades in education--his expulsion from.